Hadith #3571 - Sunan Abi Dawud - Abdullah ibn Ja'far; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Abi Sa'id; Uthman bin Muhammad bin al-Mughira عثمان بن محمد بن المغيرة بن الأخنس (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who has been appointed a judge has been killed without a knife.
Grade: Sahih